Tectonics and kinematics of curved mountain belts: examples from the Andes and the Alps - Maffione, Marco <1979> (Alma Mater Studiorum - Università di Bologna, 2009)
Curved mountain belts have always fascinated geologists and geophysicists because of their peculiar structural setting and geodynamic mechanisms of formation. The need of studying orogenic bends arises from the numerous questions to which geologists and geophysicists have tried to answer to during the last two decades, such as: what are the mechanisms governing orogenic bends formation? Why do they form? Do they develop in particular geological conditions? And if so, what are the most favorable conditions? What are their relationships with the deformational history of the belt? Why is the shape of arcuate orogens in many parts of the Earth so different? What are the factors controlling the shape of orogenic bends? Paleomagnetism demonstrated to be one of the most effective techniques in order to document the deformation of a curved belt through the determination of vertical axis rotations. In fact, the pattern of rotations within a curved belt can reveal the occurrence of a bending, and its timing. Nevertheless, paleomagnetic data alone are not sufficient to constrain the tectonic evolution of a curved belt. Usually, structural analysis integrates paleomagnetic data, in defining the kinematics of a belt through kinematic indicators on brittle fault planes (i.e., slickensides, mineral fibers growth, SC-structures). My research program has been focused on the study of curved mountain belts through paleomagnetism, in order to define their kinematics, timing, and mechanisms of formation. Structural analysis, performed only in some regions, supported and integrated paleomagnetic data. In particular, three arcuate orogenic systems have been investigated: the Western Alpine Arc (NW Italy), the Bolivian Orocline (Central Andes, NW Argentina), and the Patagonian Orocline (Tierra del Fuego, southern Argentina). The bending of the Western Alpine Arc has been investigated so far using different approaches, though few based on reliable paleomagnetic data. Results from our paleomagnetic study carried out in the Tertiary Piedmont Basin, located on top of Alpine nappes, indicate that the Western Alpine Arc is a primary bend that has been subsequently tightened by further ~50° during Aquitanian-Serravallian times (23-12 Ma). This mid-Miocene oroclinal bending, superimposing onto a pre-existing Eocene nonrotational arc, is the result of a composite geodynamic mechanism, where slab rollback, mantle flows, and rotating thrust emplacement are intimately linked. Relying on our paleomagnetic and structural evidence, the Bolivian Orocline can be considered as a progressive bend, whose formation has been driven by the along-strike gradient of crustal shortening. The documented clockwise rotations up to 45° are compatible with a secondary-bending type mechanism occurring after Eocene-Oligocene times (30-40 Ma), and their nature is probably related to the widespread shearing taking place between zones of differential shortening. Since ~15 Ma ago, the activity of N-S left-lateral strike-slip faults in the Eastern Cordillera at the border with the Altiplano-Puna plateau induced up to ~40° counterclockwise rotations along the fault zone, locally annulling the regional clockwise rotation. We proposed that mid-Miocene strike-slip activity developed in response of a compressive stress (related to body forces) at the plateau margins, caused by the progressive lateral (southward) growth of the Altiplano-Puna plateau, laterally spreading from the overthickened crustal region of the salient apex. The growth of plateaux by lateral spreading seems to be a mechanism common to other major plateaux in the Earth (i.e., Tibetan plateau). Results from the Patagonian Orocline represent the first reliable constraint to the timing of bending in the southern tip of South America. They indicate that the Patagonian Orocline did not undergo any significant rotation since early Eocene times (~50 Ma), implying that it may be considered either a primary bend, or an orocline formed during the late Cretaceous-early Eocene deformation phase. This result has important implications on the opening of the Drake Passage at ~32 Ma, since it is definitely not related to the formation of the Patagonian orocline, but the sole consequence of the Scotia plate spreading. Finally, relying on the results and implications from the study of the Western Alpine Arc, the Bolivian Orocline, and the Patagonian Orocline, general conclusions on curved mountain belt formation have been inferred.